BIMBINGAN PASCA REHABILITASI KLIEN PEMASYARAKATAN TINDAK PIDANA NARKOTIKA - Aditya Sarjana Putra; Djauhari Djauhari (Jurnal Hukum Khaira Ummah, 2017)
Increased criminal narcotics with the mode of illicit traffic, illegal transactions and misuse. The impact is 78% of deaths aged between 19-21 years. Government policy to overcome the dangers of narcotics through the guidance of correctional clients aimed at, restoring clients and productive life in the community. The purpose of this research is to know and explain the prevention system of narcotic narcotics, the implementation of post-rehabilitation guidance to correctional clients, constraints and solutions to improve guidance implementation in Class I Correctional Center of Semarang Central Java. This research uses empirical juridical approach through purposive sampling method. The results of the study, the prevention system of narcotic drug crime contains four stages of integrated therapy intervention for correctional clients namely initial acceptance, rehabilitation, post-rehabilitation and termination. Output system, client recover from narcotic dependence. Post-rehabilitation guidance prioritizes governance in procedural aspects of administration, fulfillment of facilities, planning, organizing, implementation, monitoring and monitoring and evaluation. Constraints of implementation of post-rehabilitation guidance due to internal and external factors of correctional clients. A preventative system improvement solution is the strengthening of client portfolio data during reassessment in Breathing and the need for budget politics in the inflation-friendly provision.Keywords: Post-rehabilitation guidance, narcotics crime, correctional client